2001
DOI: 10.1161/hh2001.098873
|View full text |Cite
|
Sign up to set email alerts
|

ERK and p38 MAPK, but not NF-κB, Are Critically Involved in Reactive Oxygen Species–Mediated Induction of IL-6 by Angiotensin II in Cardiac Fibroblasts

Abstract: Abstract-We recently reported that angiotensin II (Ang II) induced IL-6 mRNA expression in cardiac fibroblasts, which played an important role in Ang II-induced cardiac hypertrophy in paracrine fashion. The present study investigated the regulatory mechanism of Ang II-induced IL-6 gene expression, focusing especially on reactive oxygen species (ROS)-mediated signaling in cardiac fibroblasts. Ang II increased intracellular ROS in cardiac fibroblasts, and the increase was completely inhibited by the AT-1 blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
200
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(232 citation statements)
references
References 42 publications
(33 reference statements)
28
200
2
1
Order By: Relevance
“…We demonstrate here that ethanol differentially regulates ROS formation in the cells overexpressing ErbB2 and the cells with normal ErbB2 levels; cells with high levels of ErbB2 expression are more susceptible to ethanol-induced ROS formation. ROS may act as second messengers and activate intracellular signal cascade, including JNKs and p38 MAPK (Lo et al, 1996;Mansat-de Mas et al, 1999;Sano et al, 2001;Chen et al, 2001;Kulisz et al, 2002). However, our study indicates that catalase (a H 2 O 2 scavenger) does not affect either the activation of JNK/p38 MAPK or the cell invasion induced by ethanol.…”
Section: Formate +Etohmentioning
confidence: 49%
“…We demonstrate here that ethanol differentially regulates ROS formation in the cells overexpressing ErbB2 and the cells with normal ErbB2 levels; cells with high levels of ErbB2 expression are more susceptible to ethanol-induced ROS formation. ROS may act as second messengers and activate intracellular signal cascade, including JNKs and p38 MAPK (Lo et al, 1996;Mansat-de Mas et al, 1999;Sano et al, 2001;Chen et al, 2001;Kulisz et al, 2002). However, our study indicates that catalase (a H 2 O 2 scavenger) does not affect either the activation of JNK/p38 MAPK or the cell invasion induced by ethanol.…”
Section: Formate +Etohmentioning
confidence: 49%
“…In addition, recent studies showed that ROS could activate the MAPKs. β-Amyloid caused the production of ROS and subsequent JNK activation (Jang and Surh, 2002), and ROS induced the phosphorylation of JNK, ERK and p38 kinases (Sano et al, 2001;Lee and Esselman, 2002). These results indicated that selenite induced intracellular ROS production, and consequential activation of JNK might play a role in apoptosis induction.…”
Section: Discussionmentioning
confidence: 80%
“…Seleniteinduced cell death might be contributed by oxidative cytotoxicity. Recent studies have shown that both endogenously produced and exogenously added ROS can regulate the activity of mitogen-activated protein kinases (MAPKs) pathways that may be involved in cellular responses including proliferation, differentiation and apoptosis (Sano et al, 2001;Jang et al, 2002). MAPKs include three major kinases; extracellular signal-regulated kinase (ERK), p38 kinase and c-Jun N-terminal kinase (JNK).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that oxidative stress from exposure to excess quantities of ROS plays a major role (2,11,13,14). Redox signaling can activate macrophages including Kupffer cells and play a role in the release of cytokines that in turn influence leukocyte activation, transmigration, and target cell adhesion (13,16). The enormous numbers of leukocytes that enter the extravascular space immediately after transplantation release large quantities of ROS capable of overwhelming hepatic cell antioxidant defenses (14).…”
Section: Discussionmentioning
confidence: 99%
“…They also can, when generated in large quantities, cause direct oxidative damage to cells through iron-mediated reactions (15). Thiol donors can interrupt redox signaling pathways and thereby reduce cytokine and macrophage activation (16). In addition, thiol donors can protect cells against oxidative injury by replenishing intracellular glutathione and other endogenous thiol compounds (17).…”
Section: Ischemia͞reperfusion (I͞r) Injury Is a Serious Potential Thrmentioning
confidence: 99%